Analysis Of The Effectiveness Of Public Policy In Poverty Alleviation - Latif, Nurdianha (Generasi Sains Indonesia, 2024)
This take a look at examines the effectiveness of public policy in poverty alleviation through a complete evaluation the usage of a mixed-methods technique. Quantitative analyses, which includes descriptive statistics, paired-samples t-exams, regression analyses, ANCOVA, and Pearson correlational analyses, had been carried out to discover the relationships between socio-financial factors, coverage variables, and perceptions of poverty amongst respondents. The findings highlight big correlations between profits degree, education degree, get entry to to social offerings, and perceived policy effectiveness with perceptions of poverty. The consequences endorse that evidence-based public coverage interventions, thinking about socio-monetary context and stakeholder perceptions, play a crucial role in addressing root reasons and improving outcomes for prone populations.